Resilience of Internasional Students at Yogyakarta State University: A Phenomenology Study - Rahajeng, Anindhita Sasanti; Apriliana, Apriliana; Fathiyah, Kartika Nur (FKIP Universitas Lampung, 2024)
Resilience of Internasional Students at Yogyakarta State University: A Phenomenology Study. In addition to affecting the development of technology and information, globalization also has an impact on education. In this borderless 21st century, we have easy access to information in the field of education. The ease of internet access contributes to the spread of different cultures, which attracts students to seek learning experiences abroad. This also applies vice versa, information about Indonesian culture that is spread throughout the world raises the interest of foreign students to study in Indonesia This research uses qualitative methods, this research involves 4 foreign students as sources who come from different programs, namely UNY-DISS (Yogyakarta State University Distinguished International Student Scholarship), Dharmasiswa, and KNB (Cooperation with Developing Countries). Data collection used an open-ended interview method. Where the researcher can ask additional questions to obtain in-depth information. The validity results used member-checking, where participants were involved in providing feedback related to the data. The results of this study found that common problems often faced by international students are language barriers, cultural differences, and adapting to a new environment. International students become resilient based on the existence of positive thinking actions and a high sense of desire to learn that makes them resilient to the difficult situations they face. In general, high motivation and desire to learn increase the resilience of international students, as for the strategies they do to overcome the problems they face such as contacting friends or family, writing journals, and doing self-reflection. Keywords: resilience, international student, culture shock.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202469